Calculus-Based Physics I - Schnick, Jeffrey; Open Textbook Library (Open Textbook Library, 2008)
Calculus-Based Physics is an introductory physics textbook designed for use in the two-semester introductory physics course typically taken by science and engineering students.
1 Mathematical Prelude -- 2 Conservation of Mechanical Energy I: Kinetic Energy & Gravitational Potential Energy -- 3 Conservation of Mechanical Energy II: Springs, Rotational Kinetic Energy -- 4 Conservation of Momentum -- 5 Conservation of Angular Momentum -- 6 One-Dimensional Motion (Motion Along a Line): Definitions and Mathematics -- 7 One-Dimensional Motion: The Constant Acceleration Equations -- 8 One-Dimensional Motion: Collision Type II -- 9 One-Dimensional Motion Graphs -- 10 Constant Acceleration Problems in Two Dimensions -- 11 Relative Velocity -- 12 Gravitational Force Near the Surface of the Earth, First Brush with Newton's 2nd Law -- 13 Freefall, a.k.a. Projectile Motion -- 14 Newton's Laws #1: Using Free Body Diagrams -- 15 Newton's Laws #2: Kinds of Forces, Creating Free Body Diagrams -- 16 Newton's Laws #3: Components, Friction, Ramps, Pulleys, and Strings -- 17 The Universal Law of Gravitation -- 18 Circular Motion: Centripetal Acceleration -- 19 Rotational Motion Variables, Tangential Acceleration, Constant Angular Acceleration -- 20 Torque & Circular Motion -- 21 Vectors: The Cross Product & Torque -- 22 Center of Mass, Moment of Inertia -- 23 Statics -- 24 Work and Energy -- 25 Potential Energy, Conservation of Energy, Power -- 26 Impulse and Momentum -- 27 Oscillations: Introduction, Mass on a Spring -- 28 Oscillations: The Simple Pendulum, Energy in Simple Harmonic Motion -- 29 Waves: Characteristics, Types, Energy -- 30 Wave Function, Interference, Standing Waves -- 31 Strings, Air Columns -- 32 Beats, The Doppler Effect -- 33 Fluids: Pressure, Density, Archimedes' Principle -- 34 Pascal's Principle, the Continuity Equation, and Bernoulli's Principle -- 35 Temperature, Internal Energy, Heat, and Specific Heat Capacity -- 36 Heat: Phase Changes -- 37 The First Law of Thermodynamics
In English.
Description based on online resource
Keywords: Science -- Textbooks; Physics -- Textbooks